2022-RA-165-ESGO Surgeon-administered transversus abdominis plane (TAP) block versus placebo after midline laparotomy in gynecologic oncology: a double-blind randomized trial. (20th October 2022) - Bernard, Laurence; Lavecchia, Melissa; Trepanier, Gabrielle; Mah, Sarah; Pokoradi, Alida; McGinnis, Justin M; Alyafi, Mohammad Mohammad; Glezerson, Bryan; Nguyen, Julie; Carlson, Vanessa; Helpman, Limor; Elit, Laurie; et al.
Abstract : Introduction/Background: Surgeon-administered Transversus Abdominis Plane (TAP) block is a contemporary approach to providing postoperative analgesia. We evaluated its efficacy in a double-blind, randomized, placebo-controlled trial, hypothesizing that TAP blocks would decrease total opioid use in the first 24 hours postoperatively. Secondary outcomes included pain scores, postoperative nausea and vomiting, incidence of clinical ileus, time to flatus, and hospital length-of-stay. Methodology: Patients with a suspected or proven gynecologic malignancy undergoing surgery through a midline laparotomy at one Canadian tertiary care centre were randomized to receive bilateral surgeon-administered, transperitoneal TAP blocks with a total of 40 mL of either 0.25% bupivacaine or normal saline (placebo), prior to fascial closure. Results: 38 patients were randomized to the bupivacaine arm, and 41 patients to the placebo arm. The mean age was 60 years and mean BMI was 29.3. A supra-umbilical incision was used in 38% of cases and bowel resection was performed in 12.7% of cases. Patient and surgical characteristics were evenly distributed. The patients who received the bupivacaine TAP block required 98±59.2 morphine milligram equivalents in the first 24 hours after surgery, while the placebo group received 100.8±44 MME (p=0.85). The mean pain score at 4 hours after surgery was 3.1±2.4 in the TAP group, versus 3.1±2 in the placebo group (p=0.93). Nausea and vomiting were reported in 2.6%, vs 2.4% (p=0.95). Time to first flatus, rates of clinical ileus and length-of-stay were similar between groups. Subgroup analysis of patients with BMI <25 and patients who received an infra-umbilical incision did not show a difference. Conclusion: In this trial, surgeon-administered bupivacaine TAP block was not superior to placebo in reducing postoperative opioid requirements or improving other postoperative outcomes. These results differ from previous reports evaluating ultrasound-guided TAP block administration. Surgeon-administered TAP should not be considered standard of care in postoperative multimodal analgesia.